2018
DOI: 10.1021/acs.jpcc.8b00758
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron X-ray Photoelectron Spectroscopy Study of Electronic Changes at the ZnO Surface Following Aryldiazonium Ion Grafting: A Metal-to-Insulator Transition

Abstract: ZnO is a member of a small class of semiconductors that includes In2O3, SnO2, CdO, and InN, whose surfaces are highly unusual because their electronic bands bend downward to form a quantized potential well in which a two-dimensional electron gas is confined. At the O-polar ZnO(0001̅) surface, this effect arises from the adsorption of H adatoms which produces a hydroxyl-terminated surface. In this work, we investigate the effect of covalently anchored organic layers on the band bending at ZnO(0001̅) surfaces. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 65 publications
8
37
0
Order By: Relevance
“…Eventually, the engineering of surface trap density in ZnO NWs appears as an alternative way to tune the radius to a relevant range that is compatible with the different growth methods. It has been shown that the use of chemical adsorbates on the polar and non-polar planes of ZnO has a great effect on the nature and magnitude of the band bending [ 86 , 87 ]. The intricate nature of all these approaches represents the major difficulty to get ZnO NWs with the optimal dedicated properties.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…Eventually, the engineering of surface trap density in ZnO NWs appears as an alternative way to tune the radius to a relevant range that is compatible with the different growth methods. It has been shown that the use of chemical adsorbates on the polar and non-polar planes of ZnO has a great effect on the nature and magnitude of the band bending [ 86 , 87 ]. The intricate nature of all these approaches represents the major difficulty to get ZnO NWs with the optimal dedicated properties.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…The procedure most commonly generates loosely‐packed multilayer films covalently linked to the substrate [7] . For the O‐polar MBE ZnO used in our earlier work, X‐ray photoelectron spectroscopy (XPS) analysis, obtained with synchrotron radiation, strongly supported the presence of Zn−O−C bonds arising from covalent anchoring of aryl groups to the substrate [6] . The same bonding configuration has been demonstrated, or assumed, at other hydroxylated surfaces [8] .…”
Section: Introductionmentioning
confidence: 69%
“…The focus was to examine the mode of interaction of the film with the surface and to monitor the effect on the band bending at each crystal face. NBD was selected for the study because grafted nitrophenyl (NP) films were found to decrease the downward band bending at O‐polar MBE ZnO [6] . Our second aim was to gain insight into a very intriguing result obtained in our earlier study: during synchrotron XPS measurements, the grafted NP groups were substantially, and rapidly, converted to aminophenyl‐like groups, and concurrently, there was a dramatic change in surface band bending from downward to upward [6] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have successfully functionalized COC surfaces in absence of any plasma activation by reducing grafting of aryldiazonium salts via transient formation of the corresponding aryl radicals [16]. Widely used to modify metallic surfaces for their electro-or chemical grafting ability [17][18][19][20], these species also proved to be competent for the functionalization of polymeric surface [21]. From their reduced form, radicals covalently bind to the surface allowing various chemical functions (acids, nitro or bromo groups) to be introduced on the COC surface [16].…”
Section: Introductionmentioning
confidence: 99%